HPA e Nitro-HPA em Ambiente Semifechado Impactado por Emissão da Combustão de Diesel/Biodiesel (B5) - Sabino, Fabio Cal; Pinto, Jurandir Pereira; Piracelli, Victor Pontes; Amador, Ismael R.; Martins, Leila D.; Hoffmann, Thorsten; Solci, Maria Cristina (Orbital: The Electronic Journal of Chemistry, 2015)
In order to verify the presence of polycyclic aromatic hydrocarbons (PAHs) and nitro-PAH (NPAH) associated with the fine fraction of particulate matter (PM1.0 and PM2.5) from the combustion of diesel/biodiesel mixture (B5), daily samples were carried out in the urban bus station of Londrina. A high performance liquid chromatography with mass spectrometry (LC-APCI-MS) was used for the determination of nitro-PAH and the PAHs were determined by high performance liquid chromatography equipped with fluorescence detector (LC-FLD). 9 PAHs and 1-nitropyrene were determined. The concentrations of the PAHs with 4 to 6 rings (fluoranthene, pyrene, crysene, benzo(b)fluoranthene, benzo(k)fluoranthene and dibenzo(a,h)antharacene) were higher in comparison to the lighter PAHs (acenaphthene, fluorene and anthracene). The ∑PAH associated to the PM1.0 corresponded to 66% of the PM2.5 with concentrations that exceed the levels recommended by WHO. The diagnostic ratios (DR) of PAHs and NPAH were calculated and the results suggest diesel/biodiesel (B5) emissions. The use of biofuel in Brazil is encouraged and the monitoring of changes in emissions arising from combustion processes is important and necessary to follow the change of air quality and the impact on the environment. DOI: http://dx.doi.org/10.17807/orbital.v7i3.737